URGENCY, ROLES, AND PRACTICES OF AGRO-EDUTOURISM BASED ON INTEGRATED FARMING SYSTEM - Inanpi Hidayati Sumiasih (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2025)
Due to increasing interest in agroedutourism, sustainable agroedutourism is predicted to become a major future tourism trend in Indonesia. Expert survey results in 2023 and 2024 indicated a consistent tourism trend, with environmentally friendly tourism increasing by 46.15%. This trend is primarily driven by growing environmental awareness, which encourages tourists to choose sustainable destinations and tourism activities. A potential solution to those issues can be achieved through the  agroedutourism management using an integrated farming system. A case study conducted at Attaqie Farm Agroedutourism, which implements an integrated farming system, demonstrated that educational programs and tourism activities were highly effective in improving environmental awareness and understanding. Through hands-on activities like planting, maintaining crops, producing SNI-standard organic fertilizer, and harvesting, youth gained a deeper understanding of plant life cycles, biodiversity, and plants' role in improving air and soil quality. This management approach provides educational, functional, and aesthetic value through various integrated farming activities, including horticultural crop production (starfruit and vegetables), aquaculture cultivation using a biofloc system, and livestock farming using a raised-floor housing system. The application of compost derived from starfruit waste to support sustainable agriculture at Attaqie Farm Agro-edu-tourism showed that this practice reduced inorganic fertilizer use by 50% in pakcoy grown under a vertical cultivation system and by 25% in butternut cultivation. Furthermore, the application of liquid organic fertilizer at a concentration of 9 ml/L resulted in a mustard green shoot weight 20% higher compared to the control treatment without fertilization.